Brown Bag Lecture Series for 2015-16: Platform Cooperativism and Open Development - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2015)
The first lecture in the School of Communication Brown Bag Lecture Series will run from 12-1PM at SFU Burnaby in the Mallinson Conference Room (K8652) following the departmental meeting on November 18. For more details, please see the poster below.